Analysis on the Influence of Shaft and Cross Passage Turn to the Main Line of Ingate under Different Construction Schemes - Zhanping Song; Qi Liu; Yuwei Zhang; Xiaoxu Tian; Guannan Zhou (Advances in Civil Engineering)
In the weak stratum, the construction of ingate is a key technical problem at the place where the shaft and cross passage turn to the tunnel. Based on Lanzhou Metro, the corresponding changes to the construction plan of the ingate of the section tunnel were made. Finite element software is used to carry out three-dimensional modeling and design of subway shaft, cross passage, and tunnel structures in connected sections. The influence of the two construction schemes on surface settlement, deformation, and stress of tunnel support structure and stress conversion of ingate are compared, as well as the fitting degree between numerical simulation results and field monitoring data. Finally, the optimal scheme and key points of construction control are determined. The results show that the optimization scheme has obvious advantages in the control of surface settlement and the deformation of shaft and cross passage support. However, the difference between the stress and deformation of the tunnel supporting structure and the original plan is not obvious. Since the project focuses on shaft, cross passage, and tunnel connection section, the changed construction scheme is better.